Interpretation and reporting of mixed DNA profiles by seven forensic laboratories in the UK and Ireland. (May 2022) - Mallinder, Ben; Pope, Susan; Thomson, Jim; Beck, Lesley-Ann; McDonald, Andrew; Ramsbottom, Dorothy; Court, Denise Syndercombe; Vanhinsbergh, Des; Barber, Michael; Evett, Ian; Sullivan, Kevin; Whitaker, Jonathan
Abstract: In 2014, the UK Forensic Science Regulator (FSR) commissioned a collaborative trial to assess the methods used by forensic service providers (FSPs) in the UK and Ireland for analysis, interpretation and reporting of mixed DNA profiles. Five different mixed samples of varying complexity with supporting mock case circumstances were tested using SGMPlus™ and the newly introduced DNA-17(+) multiplexes and reported by participating laboratories. The results demonstrated a high degree of consistency in analytical methods and allele designations, but some variation in the statistical evaluation and reporting of results. Some of the differences noted were attributable to the major technology change to 17(+)-STR systems which had recently been implemented across the UK at that time. The FSR made recommendations based on the trial outcomes which were intended to produce a more consistent approach to mixtures analysis, interpretation and reporting. Four years later, the Association of Forensic Science Providers (AFSP) repeated the trial, with all major UK and Ireland FSPs (both public sector and private companies) again participating. This second trial used the same mixture set as the 2014 trial but was focussed on the methods for interpretation and evaluation. Since 2014, all UK and Ireland FSPs have implemented probabilistic statistical software using continuous models enabling statistical evaluation of more complex mixtures than was possible in 2014. The trial was therefore aimed at investigating the value of these improved capabilities and also to investigate if there appeared to be marked differences between the different software tools in use in the UK. The results demonstrate a high degree of concordance within and between FSPs and across different evaluation models, and will provide important support for the use of such models in evaluation of mixed DNA profiles. Highlights: 2014 trial assessed analysis & interpretation methods used by UK & Irish providers. Mixtures of varying complexity profiled with SGM+, GlobalFiler & DNA-17 multiplexes. Recommendations made covering interpretation, statistics, software and reporting. Repeated in 2018 with same samples to ascertain effect of recommendations. Wider use of probabilistic software, interpretation improvements & less variation.